Does Laparoscopic Adhesiolysis Decrease the Risk of Recurrence in Small Bowel Obstruction and Who Benefits the Most from Laparoscopic Approach? A literature review.: None - Furqan, Inamullah; Muhammad Burhan Khan,; ALI, SYED MUHAMMAD; Mohamed Said Ghali,; Al-Tarakji, Mohannad Al-Tarakji (European Journal of Applied Sciences, 2021)
Adhesions are usual sequelae of almost all abdominal surgery and their incidence increases with multiple explorations. One of the most common reasons for emergency general surgery is Small bowel obstruction due to adhesions (ASBO). The patients usually have classic signs and symptoms of intestinal occlusion and many will be treated by non-operative measures and ingestion of a water-soluble contrast medium. Some patients may not respond to conservative measures and will need surgical exploration and around 46% will end up in further episodes of intestinal obstruction. Laparoscopy has been utilized in these cases recently in contrast to the earlier belief that rendered it relatively contraindicated in the past. Laparoscopy has been advantageous in causing less pain, early mobilisation, and fast return of the bowel function, along with the low incidence of further adhesion formation, thus fewer recurrence rates of small bowel obstruction. We carried out a non-systemic search of the available literature (Pub Med, Google Scholar) to determine whether laparoscopic adhesiolysis decreases the risk of recurrence in patients with small bowel obstruction or not and to see which patients are suitable for laparoscopic adhesiolysis. We concluded that each patient should be individualised as this approach allows many patients with possible benefits from minimally invasive surgery. However, randomised control trials are needed to properly delineate the benefits of laparoscopic adhesiolysis over the conventional open procedures in the form of long-term outcomes and recurrence rates.